Surgery for Recurrent Uterine Cancer: Surgical Outcomes and Implications for Survival—A Case Series. Issue 4 (May 2017) - Domenici, Lavinia; Nixon, Katherine; Sorbi, Flavia; Kyrgiou, Maria; Yazbek, Joseph; Hall, Marcia; Campbell, Jeremy; Gibbons, Norma; Park, Won-Ho Edward; Gabra, Hani; Fotopoulou, Christina
Abstract : Objective: The purpose of this study was to describe the patterns of relapse in uterine cancer (UC) and the role of surgery in the recurrent setting. Methods: We describe surgical and clinical outcomes of all patients who underwent surgery for recurrent UC in a gynecological oncology tertiary referral center between May 1, 2013, and April 30, 2016. Progression-free survival and overall survival were estimated using Kaplan-Meier methods with the surgery at relapse being the starting point. Results: We evaluated 15 patients with a median age of 66 years. The predominant histology was the endometrioid variant (n = 11; 73.3%). The median interval between the end of previous treatment and relapse surgery was 24 months (range, 8–164). Locoregional pelvic recurrences were the most common type of recurrence (n = 13; 86.7%) with the para-aortic lymph node space being the most commonly affected extrapelvic site (13%). Patients predominantly presented with a multifocal pattern of relapse (n = 10; 66.7%) requiring multivisceral resections such as bowel (n = 7; 46.6%) and/or bladder/ureteric resections (n = 8; 53.3%) to achieve complete tumor clearance. All patients were operated tumor free with a 30-day major morbidity and mortality rate of 6.7% and 0%, respectively. Five patients (33.3%) received postoperative chemotherapy or radiotherapy. Five patients (33.3%) relapsed, and 3 died within a mean follow-up of 12.4 months (95% confidence interval [CI], 6.5–18.2). Two of those patients had a sarcoma. Mean progression-free survival and overall survival for the entire cohort postrelapse surgery was 21.7 months (95%CI, 13.9–29.5) and 26.0 months (95%CI, 18.4–33.7), respectively. Survival was significantly worse in patients with nonendometrioid histology ( P < 0.0001). Conclusions: Surgery for UC relapse seems feasible with acceptable morbidity and high complete resection rates despite the multifocal patterns of relapse in a selected group of patients in a reference center for gynecological cancers. Larger scale studies are warranted to establish the value of surgery at relapse for UC.